Problems of Obligation to Use Indonesian as Trademarks Against International Principles Concerning Words as Mark - Gultom, Hosiana Daniel Adrian; Sardjono, Agus; Budi, Henry Soelistyo; Yuwono, Untung (UI Scholars Hub, 2025)
The Paris Convention and Trademark Law Treaty (TLT) have emphasized the importance of distinctive characteristics of words as marks. The TRIPs have stated that trademarks are signs with distinguishing power and one of the elements are words. There are two doctrines related to the distinguishing power of words, namely the likelihood of confusion and dilution. There are also eight categories of words as trademarks with distinctive power that are recognized internationally. Indonesian trademark law has regulated distinctive characteristics of wordmarks in relation to words that cannot be registered as trademarks and words whose application for registration has been rejected. This is because Indonesia has ratified the Paris Convention, TRIPs, and TLT and harmonized its trademark law. However, there is an obligation for Indonesian citizens and its legal entities to use Indonesian words as trademarks. This article encompasses normative legal research using a statutory approach. Indonesian trademark law has accommodated the doctrine of likelihood of confusion as well as dilution. The law also implicitly recognizes five categories of wordmarks, which are: invented words, abbreviation including acronyms, arbitrary, suggestive, and generic. The obligation to use Indonesian words as trademarks limits the creation and use of words as trademarks. This norm appears to be formulated without a proper understanding of trademarks. Indonesia does not need norms like this. All trademark stakeholders must pay attention to this norm and apply for revocation.